Perkawinan Beda Agama Menurut Hukum Perdata dan Kompilasi Hukum Islam - Rahman, Arif (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Differences in a marriage are considered normal, but if the difference is religion, giving rise to an interfaith marriage, this creates problems. The aim of this research is how civil law and how the compilation of Islamic law addresses this. This research uses qualitative research by reviewing civil laws and previous research books which are strengthened by the arguments of the Koran and Hadith collected through library research which are then analyzed using descriptive analysis to produce descriptive words that can be observed according to existing events. It was concluded that society should pay more attention to the relationship between civil law and the compilation of Islamic law in marriage. Based on the research results above, it is recommended. Interfaith marriages are prohibited in Islamic law, therefore, there needs to be a positive response from the ulama to further increase Islamic Sharia regarding the prohibition of interfaith marriages. The positive legal view towards interfaith marriages is that interfaith marriages are contrary to existing norms in Indonesia, therefore law enforcers must have firmness towards interfaith marriages.